Fully integrated W-CDMA IF-receiver and IF-transmitter including IF-synthesizer and on-chip VCO for UMTS mobiles - Thomann, Wolfgang; Fenk, Josef; Hagelauer, Richard; Weigel, Robert (Proceedings of the Bipolar/BiCMOS Circuits and Technology Meeting, 2000, 2000)
A fully integrated Si-bipolar IF-receiver and IF-transmitter with on-chip synthesizer for use in third-generation W-CDMA mobiles is introduced. Both devices incorporate an on-chip IF-synthesizer with on-chip VCO tuning and tank as well as fifth order baseband filters and comply with ARIB W-CDMA and UMTS standards. The devices are mounted in a small outline, 32 pin, leadless surface mount package
elib2cris::1512001600,thomann2000
Keywords: VCO; UMTS